Fluid-structure interaction in turbulent flows; a CFD based aeroelastic algorithm using LES - Ilie, Marcel (Applied mathematics and computation, 2019)
Strong (two-way) coupling of fluid and structure presents interest to vary engineering applications, particularly when the flow is turbulent and sensitive to the structure motions. In the present work a CFD based algorithm, using large-eddy simulation, is proposed for the numerical investigation of strong aeroelastic fluid-structure coupling. The present work concerns the highly turbulent flows. The Reynolds number effect on the aeroelastic response of vertical flat plate in cross-flow is subject of investigation. The results of the present work indicate that there is a strong coupling between fluid and structure, and thus the fluid and structure influence each other in a particular manner. Also the results show that the aeroelastic response of the structure depends on the flow Reynolds number. It was observed that the structure's deformations increase with the Reynolds number.